Hyaluronidase-1 expression promotes lung metastasis in syngeneic mouse tumor models without affecting accumulation of small hyaluronan oligosaccharides in tumor interstitial fluid - Schmaus, Anja; Sleeman, Jonathan P. (Glycobiology, 2015)
Enhanced levels in tumors of hyaluronan, a glycosaminoglycan component of the extracellular matrix, and hyaluronidases such as hyaluronidase-1 (Hyal1) that degrade hyaluronan have both been linked to poor prognosis and metastasis, suggesting that the turnover of hyaluronan might contribute to tumor progression. Small hyaluronan oligosaccharides (sHA) can accumulate in tumor interstitial fluid (TIF), and have been implicated in a number of processes that drive tumor progression, including MMP expression and angiogenesis. The properties of Hyal1 suggest that it might contribute to the degradation of hyaluronan in tumors and the subsequent accumulation of sHA. Accumulation of Hyal1-produced sHA may therefore account for the association between Hyal1 and metastasis. Here we have investigated this hypothesis using mouse syngeneic breast tumor models. Specifically, we modulated Hyal1 expression and activity either in the tumor cells themselves, or in the stromal compartment by using Hyal1 knockout (KO) mice. These approaches did not change sHA levels in TIF, but nevertheless fostered metastasis to the lung in some of the models used in the study. Together, these data suggest that Hyal1 can promote lung metastasis in a manner that is not dependent on altered accumulation of sHA in TIF.